TECHNIQUE OF MODERNIZATION OF THE MODEL OF DISTRIBUTION OF RADIO WAVES IN THE MIDDLE OF THE ROOM FOR CONSTRUCTION OF A CONTROLLED AREA OF THE CORPORATE NETWORK - Бахтіяров, Денис Ілшатович; Козлюк, Ірина Олексіївна (Science-based technologies, 2019)
Today, the problem of security of information technologies is becoming increasingly significant in the use of information and telecommunication systems and networks as their role in the information society grows. This problem is of particular relevance when protecting information resources of corporate networks from information leaks due to side electromagnetic radiation from various sources. Existing models for assessing information leakage threats due to side electromagnetic emissions are generalized and there are no adequate analytical models to estimate the level of side-effects at specified points inside and outside the premises. There are no analytic approximations of the intensity of electromagnetic fields. In this case, numerical estimates of security can only be obtained through experimental studies. On the basis of the practical experiment, measurements of levels of side radiation at different distances from the source of radiation and in a wide frequency range were carried out. For the investigated corporate network, spline-approximation of experimental data was performed, on the basis of which analytical expressions were obtained for estimating the field attenuation at the studied frequencies by improving the Hata model. A comparison of experimental data and analytical calculations has shown the adequacy of the mathematical model. The developed models allow analytically to assess the level of the collateral emissions of corporate networks and can be used in the process of building a controlled area of the corporate network.